Assessment of the effectiveness of online recruitment platform of IDLC: A comparative study of the system’s effectiveness during and after Covid-19. - Hossain, Md. Nayeem (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.